2016
DOI: 10.1016/j.jmb.2016.07.013
|View full text |Cite
|
Sign up to set email alerts
|

RNA Structural Modules Control the Rate and Pathway of RNA Folding and Assembly

Abstract: Structured RNAs fold through multiple pathways, but we have little understanding of the molecular features that dictate folding pathways and determine rates along a given pathway. Here we asked whether folding of a complex RNA can be understood from its structural modules. In a two-piece version of the Tetrahymena group I ribozyme, the separated P5abc subdomain folds to local native secondary and tertiary structure in a linked transition and assembles with the ribozyme core via three tertiary contacts: a kissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Two mutants of the maltose binding protein studied by Kim et al (39) differ in inactive-to-active and active-to-inactive rates both by approximately tenfold, and thus present an opportunity to test the latter prediction. Other studies have already shown that binding mechanisms can be shifted by mutation (28) and Mg 2+ (74). …”
Section: Determination and Determinants Of Binding Mechanismsmentioning
confidence: 98%
“…Two mutants of the maltose binding protein studied by Kim et al (39) differ in inactive-to-active and active-to-inactive rates both by approximately tenfold, and thus present an opportunity to test the latter prediction. Other studies have already shown that binding mechanisms can be shifted by mutation (28) and Mg 2+ (74). …”
Section: Determination and Determinants Of Binding Mechanismsmentioning
confidence: 98%
“…Conformational dynamics also allow ribozymes to assume the many different conformations required during their multi-step catalytic cycles ( 9 11 ). Understanding RNA conformational flexibility is also critical to achieving a predictive understanding of RNA folding ( 12 14 ) and for implementing structure-based approaches in RNA-targeted drug discovery ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicate that many RNAs exist in dynamic equilibrium with alternative secondary structures that are lowly populated (population typically <15%), short lived (lifetimes typically shorter than milliseconds), and that are rich in non-canonical motifs. These conformational states are often referred to as ‘excited states’ (ESs) ( 33 , 38 ) and are increasingly implicated in the mechanisms of regulatory RNAs where they can potentially function as fast conformational switches ( 34 37 , 39 42 ) or act as intermediates during RNA tertiary folding ( 14 , 38 , 43 ).…”
Section: Introductionmentioning
confidence: 99%
“…To determine whether each element can fold by itself and to measure the cooperativity, we used mutagenesis to block one of these structural elements from folding, and then we measured folding of the non-mutated element by SHAPE footprinting. A P5abc variant that stabilizes the alternative secondary structure of P5c (U167C) ( Gracia et al, 2016 ; Silverman et al, 1999 ; Xue et al, 2016 ) displayed clear protections that indicated formation of the MC, but with an increased [Mg 2+ ] 1/2 value of 9.8 mM ( Figures 4A , 4B , S4A, and S4B; Table S1 ). The increased Mg 2+ requirement indicates that cooperativity between the native P5c secondary structure and the MC has been lost in the mutant.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the observation of a concerted transition, we wondered whether this complex transition might be mediated by structural modules within P5abc that had remained hidden in previous studies. Supporting the presence of modules, our recent work revealed that P5abc can change some of the secondary structure transiently, without the distal changes in secondary and tertiary structure ( Xue et al, 2016 ), and that it can form at least some of the native tertiary structure without the full complement of secondary structure changes ( Bisaria et al, 2016 ; Gracia et al, 2016 ).…”
Section: Introductionmentioning
confidence: 96%